Type 1 Autoimmune Pancreatitis Can Transform into Chronic Pancreatitis: A Long-Term Follow-Up Study of 73 Japanese Patients - Maruyama, Masahiro (Hindawi Publishing Corporation, 2013)
Some patients with autoimmune pancreatitis (AIP) form pancreatic stones suggestive of transformation into chronic pancreatitis (CP). The present study examined the underlying risk factors and mechanism of AIP progression to confirmed CP. We compared the clinical and laboratory parameters of subjects who progressed to confirmed CP with those of the subjucts who did not in a cohort of 73 type 1 AIP patients. A total of 16 (22%) AIP patients progressed to CP. Univariate analysis revealed that relapse was significantly more frequent in the progression group, and multivariate analysis indicated that pancreatic head swelling (OR 12.7, P = 0.023) and nonnarrowing of the main pancreatic duct in the pancreatic body (OR 12.6, P = 0.001) were significant independent risk factors for progression to CP. Kaplan-Meier testing showed that the progression rate to CP was approximately 10% at 3 years and 30% at 10 years in total AIP patients and 30% at 3 years and 60% at 10 years in subjects with both risk factors. AIP with pancreatic head swelling and a history of relapse may cause pancreatic juice stagnation and nonnarrowing of the main pancreatic duct in the pancreatic body, which can progress to advanced stage chronic pancreatitis.